Ag/CuO/MCM-48 AS A POTENTIAL CATALYST FOR THE SYNTHESIS OF SYMMETRICAL AND UNSYMMETRICAL POLYHYDROQUINOLINES - Vahdati, Narges; Mamaghani, Manouchehr; Khalili, Behzad; Tavakoli, Fateme (Journal of the Chilean Chemical Society, 2021)
Ag/CuO/MCM-48 as a heterogeneous catalyst was efficiently employed in the synthesis of diversely substituted symmetrical and unsymmetrical polyhydroquinoline by a multi-component reaction of arylaldehyde, dimedone, ethyl cyanoacetate and ammonium acetate. This novel method is simple, environmentally friendly, rapid, use a recyclable catalyst and produce the products in high to excellent yields (83-97%) and lower reaction times (17-35 min). The catalyst can be reused at least 10 times without any appreciable decrease in its catalytic activities.